2008
DOI: 10.1111/j.1440-1797.2008.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of serum von Willebrand factor and anti‐endothelial cell antibodies in patients with immunoglobulin A nephropathy are associated with intrarenal arterial lesions

Abstract: Intrarenal arterial lesions are associated with endothelial cell damage in IgAN, and vWF is a useful serological biomarker of severe intrarenal arterial lesions. AECA, especially IgG-AECA, may play an important role in the pathogenesis of intrarenal arterial damage in IgAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Plasma levels of vWF were determined using ELISA as previously described[16]. Briefly, ELISA plates were coated with rabbit anti-human vWF polyclonal antibodies (DAKO, Denmark) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma levels of vWF were determined using ELISA as previously described[16]. Briefly, ELISA plates were coated with rabbit anti-human vWF polyclonal antibodies (DAKO, Denmark) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies found that the prevalence of anti-endothelial cell antibodies (AECA) was higher in IgAN patients with severe intra-renal arterial lesions and malignant hypertension[16], [17]. AECA cannot explain all of the endothelial dysfunction in patients with IgAN.…”
Section: Introductionmentioning
confidence: 99%
“…36 Therefore, we assumed that variants in CFHR5 SCR8-9 would have a similar influence and might be associated with endothelial injury. Although we now have considerable evidence regarding endothelial injury in IgAN, [37][38][39] the underlying mechanism is still unknown. Additional functional studies are required to clarify whether our identified variants in SCR8-9 of CFHR5 influence its binding to endothelial cells and what their genetic mechanisms are in IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…Various autoantibodies, such as antiendothelial cell antibodies (AECAs) [24], antiphospholipid antibodies, antidouble-stranded DNA antibodies, antioxLDL antibodies, and antiapolipoprotein A-I antibodies [25], could directly or indirectly affect the endothelial cells and cause chronic vessel wall damage as circulating or local immune complexes, and might contribute to the pathogenesis of atherosclerosis by causing injury to the endothelium and altering the metabolism of lipoproteins involved in atherogenesis.…”
Section: Vascular Inflammationmentioning
confidence: 99%